All the Birds in the Sky - Anders, Charlie (New York : TOR Books, 2016)
"From the editor-in-chief of io9.com, a stunning novel about the end of the world--and the beginning of our futureChildhood friends Patricia Delfine and Laurence Armstead didnt expect to see each other again, after parting ways under mysterious circumstances during middle school. After all, the development of magical powers and the invention of a two-second time machine could hardly fail to alarm ones peers and families.But now theyre both adults, living in the hipster mecca San Francisco, and the planet is falling apart around them. Laurence is an engineering genius whos working with a group that aims to avert catastrophic breakdown through technological intervention. Patricia is a graduate of Eltisley Maze, the hidden academy for the worlds magically gifted, and works with a small band of other magicians to secretly repair the worlds every-growing ailments. Little do they realize that something bigger than either of them, something begun years ago in their youth, is determined to bring them together to either save the world, or plunge it into a new dark ages.A deeply magical, darkly funny examination of life, love, and the apocalypse"--
"When Patricia Delfine was six years old, a wounded bird led her deep into the forest to the Parliament of Birds, where she met the Great Tree and was asked a question that would determine the course of her life. When Laurence Armstead was in grade school, he cobbled together a wristwatch-sized device that could send its wearer two seconds into the future. When Patricia and Laurence first met in high school, they didnt understand one another at all. But as time went on, they kept bumping into one anothers lives. Now theyre both grown up, and the planet is falling apart around them. Laurence is an engineering genius whos working with a group that aims to avert catastrophic breakdown through technological intervention into the changing global climate. Patricia is a graduate of Eltisley Maze, the hidden academy for the worlds magically gifted, and works with a small band of other magicians to secretly repair the worlds every-growing ailments. Neither Laurence nor Patricia can keep pace with the speed at which things fall apart. But something bigger than either of them, something begun deep in their childhoods, is determined to bring them together. And will"--
Keywords: Magic -- Fiction; Time travel -- Fiction; Man-woman relationships -- Fiction; Fantasy fiction; Science fiction; Fantasy fiction; Fiction; Science fiction